2020
DOI: 10.1037/xge0000700
|View full text |Cite
|
Sign up to set email alerts
|

Overestimating the valuations and preferences of others.

Abstract: People often make judgments about their own and others’ valuations and preferences. Across 12 studies (N = 17,594), we find a robust bias in these judgments such that people overestimate the valuations and preferences of others. This overestimation arises because, when making predictions about others, people rely on their intuitive core representation of the experience (e.g., is the experience generally positive?) in lieu of a more complex representation that might also include countervailing aspects (e.g., is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Participants reported usefulness using our two-item usefulness scale from previous studies (Cotton swabs α = .95; Markers α = .88; Mouthwash α = .89; Sponges α = .86). They also indicated their own or their estimate of the target consumer's WTP per product on a slider from €0 to €20 (€0 to €10 for Markers), which we expected to serve as a converging measure (Jung et al 2020). Finally, we measured how sophisticated, selective, and exclusive they perceived themselves or their target to be (1 = Not at all; 7 = Very much); we averaged these three items into a perceived sophistication scale (α = .74).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants reported usefulness using our two-item usefulness scale from previous studies (Cotton swabs α = .95; Markers α = .88; Mouthwash α = .89; Sponges α = .86). They also indicated their own or their estimate of the target consumer's WTP per product on a slider from €0 to €20 (€0 to €10 for Markers), which we expected to serve as a converging measure (Jung et al 2020). Finally, we measured how sophisticated, selective, and exclusive they perceived themselves or their target to be (1 = Not at all; 7 = Very much); we averaged these three items into a perceived sophistication scale (α = .74).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we want to reflect on a recent investigation with findings similar to ours. Jung, Moon, and Nelson (2020) found that for experiences, individuals believe others will enjoy positive (and dislike negative) experiences more than they themselves would. Although the focus of their studies is on experiential enjoyment while the focus of ours is on usefulness, their proposed process is worth considering.…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Coming to social psychology results, there are several examples of replication of studies originally conducted with U.S. American undergraduate students who were successfully replicated with MTurk. For instance, overestimation of others' willingness to pay (Frederick, 2012) was successfully replicated on MTurk (Jung et al, 2019;Study 3). An ongoing mass-replication effort successfully replicated a large number of judgment and decision-making studies using Amazon MTurk, with results consistent with student samples and other online recruitment platforms such as Prolific (Chandrashekar et al, 2019;Chen et al, 2020;Collaborative Open-Science Research, 2020;.…”
Section: Participants and Proceduresmentioning
confidence: 98%
“…Similarly, research in the communications literature has shown that consumers believe that other people are more influenced by advertising than they are themselves (Davison 1983). In this vein, research in psychology has shown that people believe they are less affected by decision making biases (Pronin, Gilovich, and Ross 2004), and likewise less emotionally affected by experiences, such as a flight to Paris (Jung, Moon, and Nelson 2020). Evidently, people consider themselves to be relative stoics, believing that their personalities, preferences, and values will remain relatively the same, especially when forecasting future change (Quoidbach, Gilbert, and Wilson 2013).…”
Section: Perceived Uniqueness and Perceived Malleabilitymentioning
confidence: 99%